The Antioxidants Changes in Ornamental Flowers during Development and Senescence - Marina Cavaiuolo; Giacomo Cocetta; Antonio Ferrante (MDPI AG, 2013)
The concentration of antioxidant compounds is constitutive and variable from species to species and is also variable considering the development of the plant tissue. In this review, we take into consideration the antioxidant changes and the physiological, biochemical and molecular factors that are able to modulate the accumulation of antioxidant compounds in ornamental flowers during the whole development process until the senescence. Many ornamental flowers are natural sources of very important bioactive compounds with benefit to the human health and their possible role as dietary components has been reported. The most part of antioxidants are flower pigments such as carotenoids and polyphenols, often present in higher concentration compared with the most common fruits and vegetables. The antioxidants content changes during development and during senescence many biochemical systems and molecular mechanisms are activated to counteract the increase of reactive oxygen species and free radicals. There is a tight correlation between antioxidants and senescence processes and this aspect is detailed and appropriately discussed.